(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Today the delicate ecosystem of our earth is facing a danger of destruction on a large scale. In the name of development man has over exploited the natural resources and has polluted the environment. The problem is becoming worse due to ever expanding population of the world. The cry of the time is that we need to change the basic attitude of people towards the nature only than any step towards preserving the environment will become effective and here Environmental Education can play a very crucial role. Environmental Education is a continuous, life- long process involving education about the environment, in the environment and for the environment